2002
DOI: 10.1056/nejmoa011795
|View full text |Cite
|
Sign up to set email alerts
|

CHOP Chemotherapy plus Rituximab Compared with CHOP Alone in Elderly Patients with Diffuse Large-B-Cell Lymphoma

Abstract: The addition of rituximab to the CHOP regimen increases the complete-response rate and prolongs event-free and overall survival in elderly patients with diffuse large-B-cell lymphoma, without a clinically significant increase in toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

94
3,064
13
111

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 4,894 publications
(3,282 citation statements)
references
References 22 publications
94
3,064
13
111
Order By: Relevance
“…However, the improved survival over time was seen for both older and younger patients (Figure 1), although it was less for those very old (75+ years). This is consistent with evidence from clinical trials: survival increased for both older (60-80 years) [23] and younger (18-60 years) patients [35] after the addition of rituximab to standard chemotherapy for aggressive B-cell lymphomas, the commonest NHL subtype.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, the improved survival over time was seen for both older and younger patients (Figure 1), although it was less for those very old (75+ years). This is consistent with evidence from clinical trials: survival increased for both older (60-80 years) [23] and younger (18-60 years) patients [35] after the addition of rituximab to standard chemotherapy for aggressive B-cell lymphomas, the commonest NHL subtype.…”
Section: Discussionsupporting
confidence: 87%
“…This was approximately when rituximab was approved by the Australian Therapeutic Goods Administration for clinical use in Australia for the two commonest NHL subtypes, namely low grade or follicular lymphoma (June 1998) [3] and diffuse large B-cell lymphomas (February 2002) [4]. These results are consistent with the beneficial effects of rituximab on cancer survival observed in clinical trials [23-25]. …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It has been reported that etoposide, prednisolone, vincristine, cyclophosphamide, doxorubicin (DA‐EPOCH therapy or CDE therapy), or ganciclovir is effective for PEL,8, 9 but treatment‐based evidence for PEL and PEL‐LL has not yet been established. Expecting an effect of rituximab to CD20 antigen, we performed R‐CHOP therapy 10. There was no recurrence of the body cavity effusion after chemotherapy, and it seemed that a constant effect was provided.…”
Section: Discussionmentioning
confidence: 99%
“…Ifosfamide (IFM) administered at 1.8 mg/m 2 on days 1–3 of the 21‐day cycle was selected as a third‐line chemotherapeutic agent because it is a standard cytotoxic agent for the treatment of soft tissue sarcoma,11, 12 and CHOP (cyclophosphamide, vincristine, doxorubicin, prednisolone), which is a standard regimen for malignant lymphoma,13, 14 was selected as a fourth‐line chemotherapy treatment. However, despite this treatment, disease rapidly progressed.…”
Section: Case Reportmentioning
confidence: 99%